Age and growth of Benthosema pterotum (Alcock, 1890) (Myctophidae) in the Oman Sea. (29th October 2014) - Hosseini‐Shekarabi, S. P.; Valinassab, T.; Bystydzieńska, Z.; Linkowski, T.
Summary Juvenile and adult specimens of Benthosema pterotum (skinnycheek lanternfish) were collected during several surveys conducted on the Iranian continental shelf of the Oman Sea. Age was estimated by enumeration of growth increments in sagittae otolith sections on the assumption of their daily deposition. Three distinct growth zones in otolith microstructure (central, middle, and external) were defined. These three zones presumably represent increments deposited during successive life history stages, characterized by a different migratory behavior and depth occurrence. The number of increments in the central zone of the B. pterotum otolith (26.8 on average) was thus far one of the lowest in myctophid species studied. A negative correlation between the number of increments in the central and middle zones was observed. This might suggest a functional relation between these two periods of early life history, when fewer larvae in the epipelagic layers may be compensated by a longer non‐migratory behavior of metamorphosis larvae and early juveniles. The maximum number of growth increments in B. pterotum otoliths, i.e. 315, indicated a short lifespan of probably <1 year. The relationship between otolith length and standard length was described by linear regression model (r2 = 0.902), and between the body length and weight as an isometric growth in 274 juvenile and adult specimens (r2 = 0.922). The growth model estimated only for juveniles and adults was curvilinear (SL = 1.150 × Age0.616; r² = 0.868). Back‐calculated hatch dates might suggest a spawning season of B. pterotum from May to September, but due to the limited number of investigated specimens a prolonged spawning cannot be excluded. Further trials are needed to measure the population parameter dynamics.